2020
DOI: 10.1108/ils-12-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

“When I saw my peers annotating”

Abstract: Purpose Social annotation (SA) is a genre of learning technology that enables the annotation of digital resources for information sharing, social interaction and knowledge production. This study aims to examine the perceived value of SA as contributing to learning in multiple undergraduate courses. Design/methodology/approach In total, 59 students in 3 upper-level undergraduate courses at a Canadian university participated in SA-enabled learning activities during the winter 2019 semester. A survey was admini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(124 reference statements)
1
17
0
Order By: Relevance
“…With research focusing on literacy we move from a literary to an educational viewpoint. Literacy-oriented research considers DSR mostly as a tool for education in reading, writing, literature, and personal development, including uses of DSR in library and classroom environments (Blyth 2014;Kalir et al 2020). Indeed, some of the earliest research came from digital library studies.…”
Section: Categorizing Digital Social Reading Researchmentioning
confidence: 99%
“…With research focusing on literacy we move from a literary to an educational viewpoint. Literacy-oriented research considers DSR mostly as a tool for education in reading, writing, literature, and personal development, including uses of DSR in library and classroom environments (Blyth 2014;Kalir et al 2020). Indeed, some of the earliest research came from digital library studies.…”
Section: Categorizing Digital Social Reading Researchmentioning
confidence: 99%
“…Table 1 presents a summary of all studies. Before presenting the categories, we stress that both successes and challenges were reported across studies and any attempts to incorporate social annotation need to consider the context (Kalir et al , 2020). In this section, we spotlight learning activity designs to illuminate possibilities of social annotation in education.…”
Section: Using Web Annotation In Classroomsmentioning
confidence: 99%
“…In another study, undergraduate students reported difficulty in making distinct annotations, while some peer annotations might even impede their understanding (Thoms and Poole, 2017). Kalir et al (2020) also revealed that undergraduate students perceived divergent social qualities and benefits of social annotation, for instance, some students perceived it as useful for peer interaction but less valuable for the creation of course community. In Chen et al (2020), 5th graders felt being distracted by the competition mechanism in a gamified annotation activity given these challenges, it is important to create a feedback loop and a strategy to evaluate the use of social annotation in a particular context.…”
Section: Practical Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Web annotation is a genre of information technology that allows a user to annotate information in a shared document and anchor a discussion to the annotated information. When it is used socially in online classes, web annotation can support social reading, group sensemaking, knowledge construction, and community building (Chen, 2019;Kalir et al, 2020, Zhu et.al, 2020.…”
Section: Introductionmentioning
confidence: 99%